Export Demand of Non-Timber Forest Products: A Case Study of Cinnamon Products in Indonesia - Tanjung, Neni Christina Purba; Simangunsong, Bintang Charles Hamonangan; Manurung, Elisa Ganda Togu (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Indonesia is a major cinnamon (Cinnamomum sp.) exporting country in the world. Previous research generally measured the information on competitiveness. To improve performance, export demand behavior should also be known. This study aimed to estimate Indonesia’s cinnamon export demand function. The panel data model was investigated using panel data exports to 11 country destinations from 2010 to 2020. The classical assumption test of heteroscedasticity and autocorrelation and the model specification test were conducted. The results show that the export demand function can be represented well by the fixed-effects model, which explains about 96% of its variance. The obtained income and price elasticities were 1.08 and -0.30, indicating normal goods with inelastic export demand. It implies that countries with high-income growth should be prioritized in export expansion, and raising an export price might be a good policy option. Research on global supply chains and price volatility is needed. In addition, this study results in formulating policies related to developing the cinnamon product industry and trade. Keywords: Cinnamomum sp., data regression, demand, export, function panel